Tri- and Tetravalent Photoactivable Cross-Linking Agents - Welle, Alexandre; Billard, François; Marchand-Brynaert, Jacqueline (Synthesis, 2012)
A modular synthesis of photoactivable cross-linking agents is described, using an aromatic core, di- or triethyleneglycol spacers and photoaffinity labeling synthons that feature either perfluorophenyl azide or aryl(trifluoromethyl)diazirine motifs. Symmetrical and nonsymmetrical trivalent structures were obtained from phloroglucinol and dopamine, respectively. Symmetrical tetravalent structures resulted from the coupling of two dopamine derivatives with oxalyl chloride.
Keywords: ethers; amides; arenes; protecting groups; coupling